Improving Architecture Students’ Presentation Skills through Flipgrid during Online Learning - Arida Susyetina (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
The study aims to explore the use of Flipgrid’s features as online learning tools for the architecture students taking the English for Specific Purposes (ESP) to improve their presentation skills. The present study utilized a case study and involved twenty-six students of the Architecture Department in Universitas Kristen Duta Wacana, Yogyakarta. This study employed a qualitative method. The data were collected from students’ presentation videos uploaded on Flipgrid and interviews. The result of the study revealed that FLIPGRID plays a notable role in improving the students’ presentation skills, especially in their confidence, fluency, facial expressions, and gestures. Keywords: architecture, presentation skills, flipgrid, online learning, esp